The Influence of Compensation and Competence on Employee Performance at the Maritime Affairs and Fisheries Office of Takalar Regency - A Rahmawati; Megawhati Artiyani; Rusdiaman Rauf; Sutriani S (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
This study aims to determine the effect of compensation and competence on employee performance at the Maritime Affairs and Fisheries Office of Takalar Regency. This type of research is explanatory quantitative, with the sampling technique being a saturated sample where all the population is sampled. The sample size in this study was 43 respondents. The data analysis methods used are multiple regression, correlation coefficient, coefficient of determination, t test, and f test. The results of this study indicate that compensation and competence partially and simultaneously have a positive and significant effect on employee performance at the Maritime Affairs and Fisheries Office of Takalar Regency.